DAERAH JELAJAH DAN PERILAKU MACACA NIGRA DI KAWASAN SUAKA MARGA SATWA MANEMBO NEMBO - Adha Yakseb; Johny S. Tasirin; Marthen T. Lasut (COCOS, 2018)
ABSTRACT Macaca nigra is one of seven species spread on the island of Sulawesi. Macaca nigra has experienced a decline in population due to widespread hunting and habitat loss, so Macaca nigra is now listed as endangered. Knowledge of the home range and population of Macaca nigra in the Manembo nembo Wildlife Reserve is one of the important elements in the management of the Wildlife Sanctuary. The study was conducted in the Manembo-nembo Wildlife Sanctuary. Tomabariri District, Minahasa. The study took place in September 2018. The research method was carried out by observing one Macaca nigra group continuously throughout the day. The results of the study showed that the Macaca nigra group at the study site were 26 individuals. Macaca nigra has a specific home range The population of Macaca nigra observed having roaming rotation only takes 1 day. The Macaca nigra group observed explored an area of 23.36 ha. The trip of the Macaca nigra group in one rotation ranged from 0.28-23.36 ha from the total observations for 14 days and the Macaca nigra group in the Manembo Nembo Wildlife Sanctuary had three sleeping trees and had 7 species of feed plants which became the highest preference was Ficus benjamina and Dracontomelon dao (32.1%). The type of tree is using for sleeping tree is Ficus benjamina, Dracontomelon dao, and Pterocapus indicus.